A High-Efficiency LLC Resonant Converter For LED Driver Applications - Bas, Yuksel; Akboy, Erdem (IEEE, 2025)
High efficiency and reliable power supplies are critically important, especially for modern applications such as LED lighting systems. Resonant converters are widely used in such applications due to their ability to provide high efficiency and energy density. Among these, LLC resonant converters are the most common topology due to its soft switching ability over a wide operating range. In this paper, the analysis and design of an LLC resonant converter for LED lighting applications is presented. To validate the proposed design and analysis, a 75 W LLC resonant converter prototype is developed specifically for LED applications. Experimental results demonstrated that 96% efficiency is obtained. The experimental results confirm the accuracy of the high-efficiency and low-power-loss analysis, proving that the LLC topology delivers high performance and efficiency in LED applications.
Keywords: LED driver; LLC; resonant; soft switching; ZVS; ZCS; Computer Science; Robotics